A qualitative study of first time mothers’ experiences of postnatal social support from health professionals in England - McLeish, J; Harvey, M; Redshaw, M; Alderdice, F (Elsevier, 2020)
Problem Many women experience the transition to motherhood as stressful and find it challenging to cope, contributing to poor emotional wellbeing.